1958
DOI: 10.1099/00221287-19-3-542
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of pH on the Antibacterial Action of Subtilin A

Abstract: SUMMARY: The influence of pH value on the antibacterial action of subtilin A has been demonstrated by survivor counts, inhibition of respiration, and pH gradient plates. Staphylococcus aureus is more sensitive to subtilin as the pH value increases ; Eschmichia coli is more sensitive as the pH value decreases. The results are analogous to those obtained by other investigators working with cationic detergents, and are consistent with the hypothesis that the basic surface-active antibiotics kill bacteria by the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The effects of antimicrobial agents can also be shown with pH gradient plates (Sacks & Pence 1958;Heifitz et a/. 1974).…”
Section: Resuits and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of antimicrobial agents can also be shown with pH gradient plates (Sacks & Pence 1958;Heifitz et a/. 1974).…”
Section: Resuits and Discussionmentioning
confidence: 99%
“…shows the pH gradient determined for uninoculated plates after incubation for various intervals at 25°C. The plates are quite stable for up to 5 d, with maximal change at the pH extremes(Sacks 1956). Gradient plates are reproducible; pH determination on five different plates, 48 h after preparation on two separate days, showed an average standard deviation of 0.12 pH units at each grid centre.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…However, the variation of antibacterial activity is observed by the change of dopant, indicating that the antibacterial activity is not mainly dominated by metal ion release. Sacks et al reported that the antibacterial activity can be improved by the increase of pH in the solution . Subsequently, it was also reported that the concentration of hydroxyl defect can be controlled by solid particles such as ZnO, MgO, and so on .…”
Section: Resultsmentioning
confidence: 99%